Mutations in TMEM231 cause Joubert syndrome in French Canadians. Issue 10 (25th September 2012) - Srour, Myriam; Hamdan, Fadi F; Schwartzentruber, Jeremy A; Patry, Lysanne; Ospina, Luis H; Shevell, Michael I; Désilets, Valérie; Dobrzeniecka, Sylvia; Mathonnet, Géraldine; Lemyre, Emmanuelle; Massicotte, Christine; Labuda, Damian; et al.
Abstract : Background: Joubert syndrome (JBTS) is a predominantly autosomal recessive disorder characterised by a distinctive midhindbrain malformation, oculomotor apraxia, breathing abnormalities and developmental delay. JBTS is genetically heterogeneous, involving genes required for formation and function of non-motile cilia. Here we investigate the genetic basis of JBTS in 12 French–Canadian (FC) individuals. Methods and results: Exome sequencing in all subjects showed that six of them carried rare compound heterozygous mutations in CC2D2A or C5ORF42, known JBTS genes. In addition, three individuals (two families) were compound heterozygous for the same rare mutations in TMEM231 (c.12T>A[p.Tyr4*]; c.625G>A[p.Asp209Asn]). All three subjects showed a severe neurological phenotype and variable presence of polydactyly, retinopathy and renal cysts. These mutations were not detected among 385 FC controls. TMEM231 has been previously shown to localise to the ciliary transition zone, and to interact with several JBTS gene products in a complex involved in the formation of the diffusion barrier between the cilia and plasma membrane. siRNA knockdown of TMEM231 was also shown to affect barrier integrity, resulting in a reduction of cilia formation and ciliary localisation of signalling receptors. Conclusions: Our data suggest that mutations in TMEM231 cause JBTS, reinforcing the relationship between this condition and the disruption of the barrier at the ciliary transition zone.